Diagnostic potential of routine brain MRI and high-resolution, multi-contrast vessel wall imaging in the detection of internal carotid artery dissection - Xie, Shanshan; Ran, Yuncai; Wang, Xiao; Zhang, Yong; Fu, Qichang; Ren, Yanan; Liu, Juanfang; Teng, Zhongzhao; Cheng, Jingliang (Frontiers in Neurology, 2023)
Objective Cervical artery dissection (CAD) is one of the major causes of stroke and most commonly occurs at the site of the extracranial internal carotid artery (ICA). This study aimed to assess the value of routine brain MRI, clinical information, and high-resolution, multi-contrast vessel wall MR imaging (hrVWI) for the timely detection of ICA dissection. Methods A total of 105 patients with CAD and 105 without CAD were recruited for this study. The lesion type in the patients was determined based on images from different modalities, including brain MRI, magnetic resonance angiography (MRA), computed tomography angiography (CTA), digital subtraction angiography (DSA), ultrasonography, and hrVWI and clinical information. Each lesion was reviewed to determine the type following a stepwise procedure by referring to (1) brain MRI only; (2) brain MRI and clinical information; (3) hrVWI only; and (4) hrVWI, CTA, DSA, and clinical information. Results Typical clinical presentations of patients with potential CAD include headache, neck pain, and/or Horner's syndrome. Representative imaging signs in the brain MRI included a crescentic or circular iso- or hyperintensity around the lumen, a curvilinear and isointense line crossing the lumen, or aneurysmal vessel dilation. Based on brain MRI alone, 54.3% (57/105) of the patients with CAD were correctly classified, and the accuracy increased to 73.3% (77/105) when clinical information was combined (P < 0.001) with high specificity and low sensitivity. Further analysis showed that hrVWI had the superior capability in detecting CAD, with a sensitivity and a specificity of 95.1% and 97.0%, respectively. Conclusion The combination of brain MRI and clinical information could be used for the diagnosis of CAD; however, hrVWI should be sought for uncertain cases.